Effects of Trichinella spiralis and its serine protease inhibitors on intestinal mucosal barrier function - Ruibiao Wang; Yuheng Zhang; Zhixin Li; Jingbo Zhen; Qiankun Li; Qi Zhang; Yuqi Yang; Xueting Liu; Yixin Lu (Veterinary Research)
Abstract Trichinella spiralis (T. spiralis) is a highly pathogenic zoonotic nematode that poses significant public health risks and causes substantial economic losses. Understanding its invasion mechanisms is crucial. This study explored how the serine protease inhibitors (SPIs) secreted by T. spiralis affect the host’s intestinal epithelial barrier. Furthermore, the effects of T. spiralis infection on the jejunal barrier function in mice were investigated. The histopathological analysis indicated significant damage to the jejunum, which peaked at day 7 post-infection (dpi). The results of RT-qPCR and western blotting revealed marked reductions in tight junction proteins (ZO-1, occludin, claudin-3), mucins (MUC-1, MUC-2), and anti-inflammatory cytokines (TGF-β, IL-10) from 1 to 15 dpi. There was also increased expression of Toll-like receptors (TLR-1, TLR-2, TLR-4) and pro-inflammatory cytokines (TNF-α, IL-1β). Recombinant SPIs (rKaSPI, rAdSPI) were purified, co-cultured with intestinal epithelial cells (IPECs), and used in mouse models. The protein expression changes in IPECs and mice were consistent with those in T. spiralis-infected tissues. Both SPIs caused the down-regulation of ZO-1, occludin, claudin-3, MUC-1, MUC-2, TGF-β, and IL-10 while up-regulating TLR-4 and pro-inflammatory cytokines. As a result, the intestinal barrier was disrupted, and inflammation was exacerbated. Notably, rAdSPI had a more pronounced effect. In summary, T. spiralis infection caused significant jejunal damage and disrupted the intestinal barrier. T. spiralis-secreted SPIs, especially serpin-type serine protease inhibitors (AdSPI), were pivotal in facilitating invasion by compromising the host’s intestinal barrier and promoting inflammation. This study provides insights into T. spiralis invasion mechanisms and the potential targets for trichinellosis prevention and control.